Digital Exploitation in the Gig Economy: A Marxian Study on Platform and Online Ojek Driver Relations - M Khairullah; Romi Oktarian Novasari; Tina Kartika; Nina Yudha Aryanti (Electronic Journal of Education, Social Economics and Technology, 2025)
The transformation of the digital economy has given rise to a new work model known as the gig economy, where app-based jobs like online motorcycle taxis (ojol) are rapidly growing. Behind the narrative of flexibility and partnership offered, there lies a work relationship that creates structural inequalities between platform companies and workers. This research uses Karl Marx's social conflict theory approach to analyze the hidden forms of exploitation behind the digital work system. Through literature review and critical discourse analysis, it was found that digital communication run by platforms is one-way, relies on algorithms, and creates unequal power relations. Ojol workers do not have control over digital production tools (applications), which places them in a subordinate position. Moreover, the use of the term "partner" has proven to be an ideological instrument to cover up the inequalities in labor relations. This research concludes that the gig economy in the context of online motorcycle taxis reproduces a new form of class exploitation, with communication as a covert tool of domination. The implications of these findings emphasize the importance of fair regulation and the strengthening of worker collectives in facing platform-based work models.